Pengembangan Media Jobsheet Figma sebagai Software Alternatif dalam Desain Grafis untuk SMAN 1 Banguntapan - Muhammad Rizky Putra Wadhana; Herman Dwi Surjono (Department of Electronics and Informatics Engineering Education, 2025)
This research is designed to: (1) Develop Figma Jobsheet Learning Media in accordance with the curriculum for the tenth-grade students of SMAN 1 Banguntapan as an alternative vector-based drawing software for the subject of ICT in Graphic Design material; (2) Determine the percentage level of feasibility of Figma jobsheet as a learning tool for the application of alternative graphic design software. This research is a Research and Development (R&D) study using the ADDIE development model, which consists of five main stages: (1) Analyze; (2) Design; (3) Develop; (4) Implementation; (5) Evaluate. The type of data used is quantitative. This research was conducted using questionnaire instruments to obtain the necessary data. The data analysis technique used is quantitative descriptive analysis. The subjects of this study were the tenth-grade students of SMAN 1 Banguntapan. The results of the research show that (1) the development of the jobsheet is in accordance with the ADDIE model; and (2) based on the assessment results of material experts, covering aspects of content, instructional design, and benefits, it reached an average score of 89.08% (highly feasible), media experts reached an average score of 78.81% (feasible), and student responses obtained an average percentage of 90.24% (highly feasible), thus it can be concluded that the Figma jobsheet for SMAN 1 Banguntapan is feasible to use.